(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article talks about the features of semantic repetitions. As examples, repetitions of meanings used in oral and written speech are examined. The ideas associated with semantic repetition are confirmed. Plenasms penetrate deeply into the language. That is why such repetitions are common in the language.